Validação de aspectos semânticos em diretrizes para elaboração de Materiais Educativos Impressos para Promoção da Saúde: contribuição do Design da Informação | Semantic aspects validation in guidelines for the elaboration of Printed Educational Materials for Health Promotion: contribution of Information Design - de Freitas, Ranielder Fábio; Waechter, Hans da Nobrega; Coutinho, Solange Galvão; Gubert, Fabiane do Amaral (InfoDesign, 2020)
O presente estudo teve como objetivo aplicar o método de Validação de Conteúdos elaborado por Polit & Beck (2011) na proposta de um Guia para Elaboração de Materiais Educativos Impressos para Promoção da Saúde. Foi utilizado um comitê de juízes especialistas por meio o sistema de classificação de Pasquali (2010), nas áreas do Design da Informação e Design Gráfico, para que julgassem como adequado determinados pontos de interesse que estavam presentes no artefato em questão. Para esse momento, considerou-se o desenvolvimento de um quadro sinóptico que serviu como um norteador dos aspectos semânticos que foram apreciados, adaptados da Linguagem Visual de Horn (1998). Dessa forma, foi possível edificar soluções mais adequadas para a linguagem visual proposta no Guia, considerando que sua abordagem gira em torno do uso dos elementos da linguagem visual por não-designers, sendo tais elementos, agentes que influenciam na percepção e contribuem para promoção de ações mais responsáveis no modo de vida da população. ***** The present study aimed to validate the content of a Guide for the Development of Printed Educational Materials for Health Promotion, by judges in the areas of Information Design and Graphic Design. For content validation, seven judges participated in the study, selected via the Lattes Platform, who analyzed the material from semantic aspects. Based on the judges' considerations, a framework was developed that served as a guide for the aspects appreciated, adapted from Horn's Visual Language (1998). For consensus of the judges' judgment, the content validity index (CVI) was used. After validating the items, the Guide presented a CVI greater than 0.78, considered the gold standard. Thus, it was possible to propose an appropriate guide with accessible visual language aimed at health professionals. In the end, the content validation method proposed for the Guide proved to be reliable for identifying weaknesses and preparing the material. The comments/suggestions listed by the judges were relevant and strengthened the image representations throughout the content, based on valid guidelines about the layout of the elements on the page.